High sulfur content in distillers grains with solubles may be deleterious to beef steer performance and carcass quality - Uwituze, S.; Parsons, G.L.; Schneider, C.J.; Karges, K.K.; Gibson, M.L.; Hollis, Larry C.; Drouillard, James S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
Distillers grains with solubles are becoming an increasingly important staple of cattle diets because of rapid expansion of the fuel ethanol industry. Sulfuric acid often is used in ethanol production processes to clean and control the pH of fermenters. Consequently, distillers grains with solubles can occasionally contain high sulfur concentrations. Within the rumen, sulfur is converted to hydrogen sulfide gas by ruminal microbes. Hydrogen sulfide is eructated from the rumen and subsequently aspirated into the lungs; excess amounts of hydrogen sulfide can cause polioencephalomalacia (brainers). Polioencephalomalacia is characterized by increased respiration, decreased feed intake, listlessness, muscular incoordination, progressive blindness, and necrosis of brain tissue. Elevated sulfur levels also may have deleterious effects on cattle growth performance and carcass characteristics. The objective of this study was to evaluate effects of sulfur content in dried distillers grains with solubles on ruminal gas concentrations, feedlot performance, and carcass characteristics of finishing steers fed diets based on steam-flaked corn or dry-rolled corn.
Keywords: Beef; Sulfur; Distillers grains; Performance; Carcass quality